Comparative evaluation of zoletil and propofol induction in glycopyrrolate-xylazine-butorphanol premedicated dogs under isoflurane maintenance anaesthesia - Chaudhary, Shubham; Malik, V.; Tyagi, Surbhi K.; Goswami, Aarzoo (Indian Journal of Veterinary Surgery, 2026)
The aim of this study was to evaluate two anaesthetic protocols in mixed-breed canine patients. Twelve dogs were randomly allocated into two groups, A and B, with six animals in each group. In group A, glycopyrrolate (0.005 mg/kg body weight, i.m.) was administered first, followed 15 min later by xylazine (0.5 mg/kg, i.m.) and butorphanol (0.2 mg/kg, i.m.). After an additional 15 min, propofol (1%, i.v.) was administered to effect, and anaesthesia was maintained with isoflurane. The time of glycopyrrolate administration was considered as 0 min of the observation period. In group B, the same premedication protocol (glycopyrrolate, xylazine, and butorphanol at identical doses and intervals) was followed. After 15 min, Zoletil® 100 was administered intravenously to effect, and anaesthesia was subsequently maintained with isoflurane. Overall, the anaesthetic protocol used in group A (glycopyrrolate–xylazine–butorphanol–propofol–isoflurane) was found to be superior to that used in group B (glycopyrrolate–xylazine–butorphanol–Zoletil–isoflurane) with respect to induction quality, recovery quality, analgesic efficacy, and the dose-sparing effect on the maintenance agent. However, the group A protocol was associated with a comparatively prolonged recovery period.